Iron complexes of BIANs: Redox trends and electrocatalysis of hydrogen evolution. (1st November 2018) - Khrizanforova, V.V.; Morozov, V.I.; Khrizanforov, M.N.; Lukoyanov, A.N.; Kataeva, O.N.; Fedushkin, I.L.; Budnikova, Yu.H.
Graphical abstract: The iron (II, III) complexes was investigated in DCM and MeCN by cyclic voltammetry. The iron complexes were used as catalysts for hydrogen evolution. The very low overpotential of only 0.17-0.19 mV in MeCN was reached. Abstract: We report new iron(II, III) complexes in the framework of redox non-innocent BIAN ligands acting as highly active electrocatalysts for proton reduction. The iron complexes have been investigated by cyclic voltammetry, electron paramagnetic resonance and UV–Vis spectroscopy. The formation of Fe(III) complexes owing to electron transfer from metal to ligand has been discovered in acetonitrile and dichloromethane solutions. The hydrogen evolution catalysis is fast and efficient with a turnover frequency up to 460 s −1 and a very low overpotential of only 0.17–0.19 mV in MeCN. The catalysis is first order with respect to [catalyst] and second order with respect to [acid]. Steric hindrance of dpp-BIAN decreases the catalytic activity of the complexes. The best catalyst is the p -MeO-substituted BIAN iron complex.